Efeitos imediatos de um esforço submáximo sobre a velocidade de onda de pulso em pacientes com Síndrome de Marfan - Peres, Paulo Alberto Tayar [UNIFESP] (2010)
Purpose: Marfan syndrome is a dominant autosomal disease provoked by mutations of gene of fibrillin 1, chromosome 15, and may exhibit skeletal, ocular, cardiovascular and other manifestations. Pulse wave velocity (PWV) is used as a measure of arterial elasticity and rigidity and is related to the elastic properties of the vascular wall. As the practice of exercise is limited in this population, it was of our interest to analyze the acute effect of moderate to intensive exercise on patients with Marfan syndrome with either no dilatation of the aorta or a maximum of mild dilatation of this vessel. Methods: PWV and physiological variables were evaluated before and after the performance of sub-maximal exercise in 33 patients with Marfan syndrome and 18 controls. Results: PWV in the group with Marfan syndrome was 8.51±0.58 m/s at rest and 9.10±0.63 m/s at the end of the exercise (p=0.002); in the control group, PWV was 8.07±0.35 m/s at rest and 8.98±0.56 m/s at the end of exercise (p=0.004). The comparative analysis between groups regarding PWV at rest (p=0.519) and at the end of exercise (p=0.866) revealed no statistically significant differences. The final heart rate values in the control group were 10% higher than values in the group with Marfan syndrome (p = 0.01). Final systolic arterial pressure was higher in the control group (p=0.02). There was no difference in lactate between groups. Exercise time was greater in the control group (p=0.01). Conclusions: The behavior of aortic distensibility was similar in the patients with Marfan syndrome without or with mild dilatation of the aorta to that of the control group. The chronotropic and pressure responses were lower in patients than in control group.